Do Russian Police Fabricate Drug Offenses? Evidence From Seized Heroin's Weight Distribution. (October 2020) - Knorre, Alex
Current Russian drug policy is punitive toward people who use drugs. Moreover, criminal justice in Russia is driven by strong organizational incentives to increase performance indicators of police such as clearance rate. Taken together, these might lead to the use of extrajudicial and illegal police practices, as documented by several qualitative studies. In this article, we explore quantitative evidence of such practices, namely, weight anomalies of the seized heroin that result from minimum threshold amounts established by the law. We find significant discontinuities in the weight distribution of seized heroin near minimum threshold amounts. Placebo tests rule out alternative explanations of the discontinuity and show that the most likely source of the revealed discontinuities is police manipulations with seized heroin.